2021
DOI: 10.1039/d1na00438g
|View full text |Cite
|
Sign up to set email alerts
|

Anionic/nonionic surfactants for controlled synthesis of highly concentrated sub-50 nm polystyrene spheres

Abstract: Polystyrene nanospheres are of great importance in 3D hard templating along with many other fields like pharmaceuticals and coatings. Therefore, it is important to be able to prepare polystyrene beads...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The maximum recorded Li + adsorption capacity with the q e values as mentioned in Figure 5b was 0.72 mg/g, 1.34 mg/g, 2.15 mg/g, and 1.97 mg/g for the CaO-NPs, Ag-CaO-NPs, PVP@Ag-CaO, and SDS@Ag-CaO nanocomposites, respectively. The highest Li + adsorption potential was recorded at pH 10 for the SDS@Ag-CaO nanocomposites compared to PVP@Ag-CaO, which may be due to several reasons: (i) the anionic nature of SDS (anionic surfactant), whereas PVP is a non-ionic surfactant, and (ii) the presence of a very strong negatively charged sulfonate group in SDS, which is not present in the PVP surfactant [66]. Zheng et al [67] reported a similar type of pH effect trend by using the designed lanthanide-doped ion sieves.…”
Section: Effect Of Ph On LI + Adsorption Performancementioning
confidence: 96%
“…The maximum recorded Li + adsorption capacity with the q e values as mentioned in Figure 5b was 0.72 mg/g, 1.34 mg/g, 2.15 mg/g, and 1.97 mg/g for the CaO-NPs, Ag-CaO-NPs, PVP@Ag-CaO, and SDS@Ag-CaO nanocomposites, respectively. The highest Li + adsorption potential was recorded at pH 10 for the SDS@Ag-CaO nanocomposites compared to PVP@Ag-CaO, which may be due to several reasons: (i) the anionic nature of SDS (anionic surfactant), whereas PVP is a non-ionic surfactant, and (ii) the presence of a very strong negatively charged sulfonate group in SDS, which is not present in the PVP surfactant [66]. Zheng et al [67] reported a similar type of pH effect trend by using the designed lanthanide-doped ion sieves.…”
Section: Effect Of Ph On LI + Adsorption Performancementioning
confidence: 96%
“…Liu et al extended the classical Stöber method that is most commonly used in preparing inorganic nanospheres to synthesize the resorcinol formaldehyde (RF) resin monodisperse spheres [49]. Al Najjar et al refined the reaction parameters of emulsion polymerization and obtained a high concentration of PS monodisperse spheres without any filtration or centrifuging [50]. Wang and coworkers reported a solvent/antisolvent self-assembly method that narrowed down the dispersion of lignin spheres [51].…”
Section: Polymer Spheresmentioning
confidence: 99%